IMPLEMENTASI MANAJEMEN PEMASARAN PENDIDIKAN DI PONDOK PESANTREN DARUSSALAM PUNCAK SILIRAGUNG BANYUWANGI - Nur Khafidz Nizam Fahmi; Alim Mujahidin (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2022)
With this, the researcher aims to find out: 1. How is marketing management planning in the global competition in PP Darussalam Puncak? 2. How to implement the implementation of marketing management in a global competition at PP Darussalam Puncak. 3. How to control marketing management in a global competition at PP Darussalam Puncak. In this study, it can be concluded as follows: 1) In the education marketing planning process, PP Darussalam Puncak is very concerned about the quality of educational institutions and focuses on education customers. 2) In the process of implementing education marketing, PP Darussalam Puncak formed a committee and collaborated with alumni and community leaders. 3) PP Darussalam Puncak performs control and has an annual control plan to facilitate the control carried out. The results of this control can be used as a reference for future marketing plans.